Investigating students’ self-perceived affective learning during classroom interaction involvement at a South African University - Moroaswi, O. M.; Segabutla, M. H.; Olifant, F. M.; Cekiso , M. P.; Dieperink, M. (South African Journal of Higher Education, 2023)
Despite the importance of affective learning as a gateway to learning, it has been neglected in university curricula in many parts of the world. Subsequently, in formal classroom teaching, the bulk of the teachers’ efforts typically go into the cognitive aspects of the teaching and learning and most of the classroom time is earmarked for cognitive outcomes. However, research has shown that the affective domain develops well-rounded students with broad abilities and consequently many scholars advocate for the incorporation of the affective domain in university curricula. Therefore, the aim of this article was to establish and understand the self-perceived affective learning of the university students in order to match their emotions to the process of teaching and learning. The study was quantitative in nature and a survey design was followed. The Attribution theory was used to anchor the study. A randomly selected sample of 127 first-year students registered for Linguistics was used to collect data. A questionnaire was used to collect data and the Statistical Package for the Social Sciences (SPSS) was used to analyse data. With regards to students’ self-perceived perceptiveness during classroom interaction involvement, the findings revealed that the majority of students were very perceptive to the meaning of others’ behaviour in relation to themselves and the situation. Concerning the students’ self-perceived attentiveness during classroom interaction involvement, the majority of students reported that they were very observant of others’ reactions while speaking during classroom conversation. Finally, regarding students’ self-perceived responsiveness during classroom interaction involvement, the students indicated that they felt confident during their conversation in class, and were sure of what to say and do.